THE SIGNIFICANCE OF BALANCING LIFE IN SURAH AL-QASHASH VERSE 77 - Halya Millati; Mohammad Arif (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
Abstract The theological debate between Jabbariyyah (pre-destination) and Qadariyyah (free will) was polarized during the Covid-19 pandemic. Some Muslims tend to be fatalists (pre-destination), and the others believe in free will on the face of this pandemic. Of course, this is not in line with the moderate principles that Islam brings. Because, in various texts of the Quran, Allah command to balance the welfare of duniawi and hereafter (ukhrawi) life. Among these texts is what Allah said in Surah Al-Qashash verse 77 regarding the command to seek the afterlife and not forgetting sustenance in the world. With the ma'na-cum-maghza approach, this paper answers the significance of the current meaning of the commandment. There are three important points to reveal. The first, al-ma'na al-ta rikhi (historical meaning) of the verse, including advice to Qarun to seek the afterlife's reward without ignorance of the world, good doing, and prohibition of destroying the earth. The second, al-maghza al-tarikhi (the significance of historical phenomena), namely the message to Quraish community to take the middle path by following the Prophet's preaching and still pay attention to the life of the world, and to help others when possible. The third, al-maghza al-mu'as}ir (dynamic significance), namely the principle of the balance of life in the world and the hereafter. Keywords: balancing life; ma'na cum-maghza; Al-Qashash verse 77. Abstrak Perdebatan teologis antar paham Jabbariyyah (pre-destination) dan Qadariyyah (free will) terpolarisasi kembali saat masa pandemi Covid-19. Sebagian umat Islam cenderung bersikap fatalis (pre-destination), dan sebagian lagi meyakini kehendak bebas (free will) dalam menghadapi pandemi. Tentu saja hal ini tak sejalan dengan prinsip moderat yang dibawa Islam. Karena, di berbagai teks Al-Quran, Allah mengajak untuk menyeimbangkan kesejahteraan kehidupan duniawi dan ukhrawi. Di antara teks tersebut ialah apa yang Allah firmankan dalam Surah Al-Qashash ayat 77 tentang perintah untuk mencari bagian akhirat dan tidak melupakan rezeki di dunia. Dengan Pendekatan ma’na cum-maghza, tulisan ini menjawab bagaimana signifikansi makna perintah tersebut saat ini. Ada tiga poin penting yang diungkap. Pertama, al-ma’na al-tarikhi (makna historis) ayat tersebut, yakni perintah terhadap Qarun untuk mencari ganjaran akhirat tanpa abai terhadap dunia, berbuat baik, dan larangan merusak bumi. Kedua, al-maghza al-tarikhiy (signifikansi fenomenal historis), yakni pesan terhadap masyarakat Quraish untuk mengambil jalan tengah dengan mengikuti dakwah Nabi dan tetap memerhatikan kehidupan dunia, dan menolong orang lain saat diberi kelapangan. Ketiga, al-maghza al-mu’as}ir (signifikansi dinamis), yakni prinsip keseimbangan kehidupan dunia dan akhirat. Interpretasi demikian ini menjadi alternatif yang bisa menengahi kontradiksi dua paham di atas. Kata kunci: Keseimbangan hidup; ma’na cum-maghza; Al-Qashash ayat 77